Pengaruh Religiusitas, Norma Subjektif, dan Harga Produk terhadap Keputusan Pembelian Kosmetik Halal ditinjau dari Purchase Intention - Chusna, Alivia Fitri Fatayatul; Mustofa, Rochman Hadi (Ekonomis: Journal of Economics and Business, 2024)
This research aims to examine the influence of religiosity, subjective norms, and price on the decision to purchase halal cosmetics among UMS Accounting Education students, as well as to test their influence indirectly through the purchase intention of UMS Accounting Education students. The research method used was quantitative or survey by distributing questionnaires, and sampling was carried out using a simple random sampling technique with a Structural Equation Modeling (SEM) analysis model using smart PLS 3.0. This research was conducted with a population of 360 using the Slovin method, so the sample results were 189 majoring students. UMS Accounting Education Class 2019-2022. The findings of this study indicate that there is a positive and statistically significant impact of the p-value coefficients on all directly connected variables. The findings of this study indicate that all variables exhibiting an indirect impact exert a noteworthy influence on purchasing decisions via purchase intention, with the exception of the religiosity variable. The religiosity variable does not demonstrate a significant effect on purchasing decisions through purchase intention, as evidenced by a coefficient p value below 0.05